Cholinergic and ghrelinergic receptors and KCNQ channels in the medial PFC regulate the expression of palatability - Parent, Marc A.; Amarante, Linda M.; Swanson, Kyra; Laubach, Mark (Frontiers in Behavioral Neuroscience, 2015)
The medial prefrontal cortex (mPFC) is a key brain region for the control of consummatory behavior. Neuronal activity in this area is modulated when rats initiate consummatory licking and reversible inactivations eliminate reward contrast effects and reduce a measure of palatability, the duration of licking bouts. Together, these data suggest the hypothesis that rhythmic neuronal activity in the mPFC is crucial for the control of consummatory behavior. The muscarinic cholinergic system is known to regulate membrane excitability and control low-frequency rhythmic activity in the mPFC. Muscarinic receptors (mAChRs) act through KCNQ (Kv7) potassium channels, which have recently been linked to the orexigenic peptide ghrelin. To understand if drugs that act on KCNQ channels within the mPFC have effects on consummatory behavior, we made infusions of several muscarinic drugs (scopolamine, oxotremorine, physostigmine), the KCNQ channel blocker XE-991, and ghrelin into the mPFC and evaluated their effects on consummatory behavior. A consistent finding across all drugs was an effect on the duration of licking bouts when animals consume solutions with a relatively high concentration of sucrose. The muscarinic antagonist scopolamine reduced bout durations, both systemically and intra-cortically. By contrast, the muscarinic agonist oxotremorine, the cholinesterase inhibitor physostigmine, the KCNQ channel blocker XE-991, and ghrelin all increased the durations of licking bouts when infused into the mPFC. Our findings suggest that cholinergic and ghrelinergic signaling in the mPFC, acting through KCNQ channels, regulates the expression of palatability.